Online drug user-led harm reduction in Hungary: a review of "Daath" - Moro L; Racz J (BIOMED CENTRAL LTD, 2022)
Harm reduction has been increasingly finding its way into public drug policies and healthcare practices worldwide, with successful intervention measures justifiably focussing on the highest-risk groups, such as injecting drug users. However, there are also other types of drug users in need for harm reduction, even though they pose less, low, or no public health risk. Occasionally, drug users may autonomously organise themselves into groups to provide advocacy, harm reduction, and peer-help services, sometimes online. The www.daath.hu website has been operated since 2001 by the "Hungarian Psychedelic Community", an unorganised drug user group with a special interest in hallucinogenic and related substances. As of today, the website serves about 1200 visitors daily, and the online community comprises of more than 8000 registered members. The Daath community is driven by a strong commitment to the policy of harm reduction in the form of various peer-help activities that aim to expand harm reduction without promoting drug use. Our review comprehensively summarises Daath's user-led harm reduction services and activities from the last ten years, firstly outlining the history and growth phases of Daath, along with its self-set guidelines and policies. Online services (such as a discussion board, and an Ecstasy pill database) and offline activities (such as Ecstasy pill field testing, and a documentary film about psychedelics) are described. In order to extend its harm reduction services and activities in the future, Daath has several social, commercial, and legislative challenges to face. Starting with a need to realign its focus, outlooks for the upcoming operation of Daath are pondered. Future trends in harm reduction, such as separating harm-decreasing from benefit-increasing, are also discussed. We aim to share these innovative harm reduction measures and good practices in order to be critically assessed, and if found useful adapted and applied elsewhere.